Resources of Iranian agarics (Basidiomycota) with an outlook on their antioxidant potential - Ghobad-Nejhad, Masoomeh; Antonín, Vladimír; Moghaddam, Mohaddeseh; Langer, Ewald (Frontiers in Microbiology, 2022)
Agaric fungi are an important group of macromycetes with diverse ecological and functional properties, yet are poorly studied in many parts of the world. Here, we comprehensively analyzed 558 agaric species in Iran to reveal their resources of edible and poisonous species as well as their ecological guilds and luminescence potential. We also made a thorough survey of the antioxidant activity of the species. Phylogenetic relationships were reconstructed based on nuclear ribosomal LSU and ITS sequences. Our results reveal that agarics of Iran comprise about 189 edible, 128 poisonous, 254 soil saprotrophic, 172 ectomycorrhizal, 146 wood-inhabiting, 18 leaf/litter-inhabiting, 9 parasitic, and 19 luminescent species. Twenty percent of the Iranian agaric species possess antioxidant activity, phylogenetically distributed in four orders and 21 agaric families. About 5% of the antioxidant species can be considered strong antioxidants, many of which are also edible and could be utilized to develop functional foods. This is the first study combining the phylogeny and antioxidant potential of agaric mushrooms on a large scale, and the obtained results would guide the selection of agaric taxa to be examined in the future for taxonomic revisions, biotechnological applications, and applied phylogeny studies.